2019
DOI: 10.25103/jestr.121.22
|View full text |Cite
|
Sign up to set email alerts
|

Experimental of Vision-based Lane Markings Segmentation Methods in Lane Detection Application

Abstract: Lane departure collisions have contributed into the traffic accidents that cause millions of injuries and tens of thousands of casualties per year worldwide. Hence, a vision-based lane detection framework (VBLD) is proposed to detect lane markings on the road for unindented lane departure. The proposed VBLD framework is composed of colour space conversion, region of interest, lane marking segmentation, Hough transformation and peak detection, reverse Hough transformation, and draw detected lines on original im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The results showed that the real-time lane detection method on the ground of improved fusion and enhanced sampling algorithm achieved satisfactory lane detection results in lane detection frames under different road conditions. Evaluation metrics include detection rate, false positive rate (FP), and false negative rate (FN) [7]. T. T. Zhang and other researchers proposed a longitudinal scanning line LiDAR camera model to solve the problem of extracting the trajectory of urban main road intersections.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…The results showed that the real-time lane detection method on the ground of improved fusion and enhanced sampling algorithm achieved satisfactory lane detection results in lane detection frames under different road conditions. Evaluation metrics include detection rate, false positive rate (FP), and false negative rate (FN) [7]. T. T. Zhang and other researchers proposed a longitudinal scanning line LiDAR camera model to solve the problem of extracting the trajectory of urban main road intersections.…”
Section: Related Workmentioning
confidence: 99%
“…By using these parameters, the collected point cloud data can be projected onto the image to complete the registration between the point cloud and the image. The projection equation is represented as equation (7).…”
Section: Binternal Point Extraction Of Traffic Markings On the Ground...mentioning
confidence: 99%
See 1 more Smart Citation
“…The current lane departure warning system mainly consists of the environment detection component, namely the vision sensor, which detects the lane edge, lane mark-ing, and road contour [9]. Lane departure warnings are usually applicable only on highways with distinct lane markings, and the systems may be affected due to invalid activity conditions on the road.…”
Section: Introductionmentioning
confidence: 99%